Moderasi Mazhab Sebagai Metode Normatif Dalam Fiqh Ekonomi Islam Kontemporer - Ardiyah, Anis; Muhajir; Nursobah, Achmad (Kartika: Jurnal Studi Keislaman, 2025)
The exclusivism of Islamic legal schools often limits the adaptability of Islamic jurisprudence in addressing the complex realities of the contemporary Islamic economy. This study departs from the academic concern that rigid adherence to a single madhhab potentially causes legal stagnation in responding to global financial challenges. The research aims to formulate a conceptual and methodological framework for madhhab moderation as an epistemic foundation for contemporary Islamic economic jurisprudence. Using a qualitative method with critical-comparative analysis of classical and contemporary fiqh literature, this study synthesizes diverse madhhab approaches through maqāṣid al-sharī‘ah, maṣlaḥah, and ḥikmah principles. The findings reveal that madhhab moderation enables integrative, context-sensitive legal reasoning that harmonizes textual sources, socio-economic contexts, and higher legal objectives. This study proposes madhhab moderation as a model of tarjīḥ wasatī as a new methodology for formulating inclusive, responsive, and sustainable Islamic economic fatwas. The implications extend to the renewal of tarjīḥ and talfīq methods, strengthening trans-madhhab collaboration, and enhancing the global relevance of Islamic economic jurisprudence